Performa Produksi Babi Ras Persilangan Umur 2-6 Bulan yang Diberi Ransum dengan Suplementasi Mineral-Vitamin Kompleks - Rusmawan I K. A.; N. W. Siti; I G. N. G. Bidura (Jurnal Peternakan Tropika, 2018)
This study aims to determine the effect of mineral-vitamin complex supplementation in the ration to growth performance boar crossbreed the age of 2-6 months. The design used was a randomized block design (RBD) comprising 3 treatments and 4 groups as replication, clustering based on weight. The treatments were attempted diets without supplementation of mineral-vitamin complex as the control (A), the diets with 0.10% mineral supplementation-vitamin complex (B), and 0.20% diets supplemented mineral-vitamin complex (C). The variables measured were final body weight, weight gain, feed intake and feed conversion ratio. The results showed that supplementation of mineral-vitamin complex at the level of 0.10% and 0.20% (P <0.5) can improve the final body weight, weight gain and feed efficiency in use but not significantly (P> 0.5) increases feed intake in pigs race crosses the age of 2-6 months. It was concluded that supplementation of 0.10 to 0.20% mineral-complex vitamins in the ration can increase the final body weight, weight gain and feed efficiency in the use of the boar cross breed. Key words: supplementation, pig crossbreeds, carcass production, mineral-vitamin complex